Drug Utilization Pattern by Using WHO Core Prescribing Indicators in Orthopedics and Obstetrics / Gynecology Departments of a Tertiary Care Hospital - Karki, Naresh; Prasad, Pravin; Joshi, Ruban Raj; Shrestha, Buddhi Kumar (Journal of Lumbini Medical College, 2019)
DOI: https://doi.org/10.22502/jlmc.v7i1.280Introduction: Drug utilization research is an important tool to provide facility of rational use of drugs. In low income countries irrational use of drugs is a common problem like overuse of drugs and inappropriate use of antibiotics, leading to poor treatment outcome and increased burden of treatment. This study was conducted to provide understanding of drug utilization pattern by using WHO Core Prescribing Indicator.Methods: This study was conducted in Orthopedics and Obstetrics / Gynecology departments. Patients visiting these Out Patient Departments with at least one drug on prescription form were included in the study. Further, information related to WHO Core Prescribing Indicators were collected in pre-designed proforma.Results: Average number of drugs prescribed per prescription was 2.6. Means of number of drugs prescribed in Orthopedics and Obstetrics / Gynecology departments were 2.9 and 2.3 respectively (p < 0.001). Drugs prescribed in generic name and from essential drug list was 41.4% and 34.3% respectively. Prescription forms with generic name in Orthopedics department were significantly more compared to Obstetrics / Gynecology department (p = 0.00002). However, there was an increased tendency to prescribe drugs from essential drug list in Obstetrics / Gynecology department compared to Orthopedics department (p < 0.001).Conclusion: Drugs were prescribed by generic name and from essential drug list, but this was not sufficient to meet the ideal values of WHO Core Prescribing Indicator. Therefore, prioritization on prescribing drugs by generic name and from essential drug list by respective departments to achieve the standards of WHO needs to be encouraged.